Atmospheric preservation of CH4 hydrate above ice point: A potential application for high-density natural gas storage under moderate conditions. (1st June 2021) - Wang, Shenglong; Xu, Jian; Fan, Shuanshi; Wang, Yanhong; Lang, Xuemei; Yu, Chi
Highlights: Hydrate coating is proved effective for the suppression of CH4 hydrate dissociation. CH4 hydrate is successfully preserved at 1 atm and a temperature up to 284 K. CH4 storage capacity up to 146 V CH4 (STP)/ V water is achieved at 275 K, 0.1 MPa. Abstract: Clathrate hydrates is an ideal host for natural gas, by entrapping CH4 molecules in cage-like structures composed of hydrogen-bonded water molecules, natural gas can be stored in solid form with high density. However, the suppression of hydrate dissociation under moderate thermodynamic conditions is still challenging. In this study, to increase the preservation stability of CH4 hydrate at atmospheric pressure, a new surface-treatment method was proposed by coating CH4 hydrate with CP-CH4 hydrate. CH4 hydrate pellets formed from ice powder or 0.03 wt% Sodium dodecyl sulfate (SDS) solution were mechanically pressurized with CP to form hydrate pellets. The presence of CP-CH4 hydrate layer on the sample surface was confirmed by Raman spectroscopy, and the hydrate pellet was successfully preserved under superheated conditions, i.e., 0.1 MPa − 0.3 MPa, 279 K − 284 K with a storage volume density up to 146 V CH4 (STP)/ V water, and the accumulated CH4 loss was less than 0.3 mol% for hydrate pellet formed from ice powder, and 3 mol% for hydrate pellets formed from SDS solution for at least 8 h.